Usefulness of Home Overnight Pulse Oximetry in Patients with Suspected Sleep-Disordered Breathing - Cristina Esteban-Amarilla; Silvia Martin-Bote; Antonio Jurado-Garcia; Ana Palomares-Muriana; Nuria Feu-Collado; Bernabe Jurado-Gamez (Canadian Respiratory Journal)
Background and Objective. To determine the diagnostic yield of nocturnal oximetry versus polygraphy for the diagnosis and classification of sleep apnea hypopnea syndrome (SAHS). Methods. Prospective study conducted in a university hospital. Subjects with a clinical suspicion of SAHS were included. All of them underwent home polygraphy and oximetry on the same night. A correlation was made between the apnea-hypopnea index (AHI) and the oximetry variables. The variable with the highest diagnostic value was calculated using the area under the curve (AUC), and the best cut-off point for discriminating between patients with SAHS and severe SAHS was identified. Results. One hundred and four subjects were included; 73 were men (70%); mean age was 52 ± 10.1 years; body mass index was 30 ± 4.1, and AHI = 29 ± 23.2/h. A correlation was observed between the AHI and oximetry variables, particularly ODI3 (r = 0.850; P<0.001) and ODI4 (r = 0.912; P<0.001). For an AHI ≥ 10/h, the ODI3 had an AUC = 0.941 (95% confidence interval (CI) = 0.899–0.982) and the ODI4, an AUC = 0.984 (95% CI = 0.964–1), with the ODI4 having the best cut-off point (5.4/h). Similarly, for an AHI ≥ 30/h, the ODI4 had an AUC = 0.922 (95% CI = 0.859–0.986), with the best cut-off point being 10.5/h. Conclusion. Nocturnal oximetry is useful for diagnosing and evaluating the severity of SAHS. The ODI4 variable was most closely correlated with AHI for both diagnosis.